The impact of non-performing financing and operational efficiency on the stability of Islamic banks in Persian Gulf countries - Salsabilla, Lathifah Zaina; Jaya, Tiara Juliana (Universitas Islam Indonesia, 2024)
IntroductionIslamic banking has become an integral part of the global financial system, particularly in the Persian Gulf region. Due to its reliance on profit-sharing and non-interest-based operations, Islamic banking faces unique challenges in maintaining stability, particularly when financing problems arise. ObjectivesThis study analyzes the effect of Non-Performing Financing (NPF), operational efficiency, and input-output optimization on the stability of Islamic banks in the Persian Gulf countries. MethodThis study employs a quantitative approach using panel data regression models, specifically the random effects model (REM), to analyze data from 27 Islamic banks in eight Persian Gulf countries. The study includes classical assumption tests, such as normality, multicollinearity, and heteroscedasticity, followed by hypothesis testing using t-tests and F-tests.ResultsThe results indicate that both NPF and efficiency have significant negative impacts on the stability of Islamic banks. The t-test reveals that NPF has a probability value of 0.0447 and a negative coefficient, suggesting that higher NPF levels reduce bank stability. Similarly, operational efficiency, as measured by the input and output variables, also shows a negative influence on stability, with a probability value of 0.0435. The F-test confirms that NPF, input, and output significantly affect Islamic bank stability, with an F-statistic probability value of 0.038223.ImplicationsThese findings have important implications for the management of Islamic banks in the Persian Gulf countries. Effective management of NPF is critical for maintaining stability, and operational improvements in efficiency can also enhance financial performance. Islamic banks should focus on improving their financing practices, including better monitoring problematic loans and diversifying revenue streams to reduce reliance on financing income.Originality/NoveltyThis study contributes to the understanding of Islamic bank stability by exploring the combined effects of Non-Performing Financing (NPF) and operational efficiency on bank financial health. By focusing on Islamic banks in the Persian Gulf countries, this study highlights region-specific challenges and offers strategies for mitigating financial risks and enhancing bank resilience through better management of NPF and operational efficiency.